HUBUNGAN STRES DAN MOTIVASI KERJA DENGAN HASIL KERJA OPERATOR JAHIT PO. SEVENTEEN GLORY SALATIGA - Intan Maghfiroh; Ida Wahyuni; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2017)
Competition in textile industry is increasing. Workers play an important role to increase the company’s production. Worker productivity can be affected by stress and work motivation. The aim of this study was to analyze the relations between stress and work motivation with work result in sewing operators. The dependent variabel is work result while the independent variabel are stress and work motivation. This type of research is explanatory research with cross sectional approach. Population of this research is sewing operators totaling 35 people. The sample in this study were drawn from total population. The process of data collection using work result table and questionnaires. Data were analyzed using Rank Spearmen correlation test. Statistical results showed that there are correlation between stress (p = 0,000) and work motivation (0,003) with sewing operators work result. Business owner should give material or non material reward for workers who have a good work result and should give trainings about sewing technique to improve production result.